P39 Emergency admissions to hospital for older people with copd during the reshaping care for older people programme (rcopp): an ecological study. (2nd September 2017) - Levin, KA; Crighton, EM
Abstract : Background: The RCOPP was a national programme aimed at enabling older people to stay independent and well at home. Three of the interventions funded by the RCOPP in Glasgow City targeted COPD. This study aims to describe emergency admissions (EAs) for those with COPD in Glasgow City during the RCOPP. Methods: COPD EAs were defined using a primary diagnosis of COPD, while EAs for those with COPD were defined using any of the 6 diagnostic fields. Monthly standardised rates of emergency admission between April 2011 and March 2015 were calculated, for residents of Glasgow City aged 65 years+. Multilevel Zero-inflated Negative Binomial models for EAs nested by datazone adjusted for sex, 5 year agegroup, area-level deprivation (SIMD quintile), season, month and month squared. Relevant interventions were entered into the models, to test association with the two outcomes by time and location. Results: COPD EAs first rose, from April 2011 until October 2012, then fell until March 2015. When modelled, both month (RR for month 12 relative to month 1% and 95% CI=1.08 (0.996, 1.17)) and month squared (RR=0.998 (0.996, 0.999)) were significant, with risk of admission falling below the baseline figures by October 2013 and continuing to reduce thereafter. EAs for COPD patients, however, had the opposite trend, first falling between April 2011 and February 2013, then rising until March 2015, although never reaching the level of April 2011. Under the model, month (RR=0.92 (0.87, 0.97)) and month squared (RR=1.002 (1.001, 1.003)) were both significant. However, this increase was only in the North East and North West sectors of Glasgow. EA for COPD patients reduced in the South, with particularly large reductions from July 2012. When included in the model, the Community Respiratory Team, in the North West, was associated with reductions in COPD EAs (RR=0.89 (0.82, 0.97)) from the point of full staffing) and increases in EAs for COPD patients (RR=1.11 (1.03, 1.20)). Two other projects were also potentially associated with increases in EAs for COPD. Conclusion: COPD EAs reduced from the end of 2012, in line with all-cause EAs shown previously. The timing and geography suggest these reductions may be due to the Community Respiratory project which helps people to manage their symptoms at home. EAs for COPD patients, however, increased from around the same time. This or another RCOPP service may have raised awareness of other health concerns or health more generally, increasing EAs for these patients.